2022
DOI: 10.1002/app.53033
|View full text |Cite
|
Sign up to set email alerts
|

Rigid‐soft’ synergistic effects to improve the microstructure and superflexibility properties of aramid nanofiber aerogel

Abstract: Designing aramid nanofiber (ANF) aerogel with excellent microstructure and high thermal insulation property is benefit for applications in integrated thermal management system. To obtain a structurally controllable ANF‐based aerogel, the cellulose nanofiber (CNF) and poly (vinyl alcohol) (PVA) were ‘stiff–soft’ synergistic to improve the microstructure. The cobweb like structures distributed in the honeycomb layered pores of the CNF/PVA/ANF composite aerogel which was conducive to the performance and applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…At the same time, ZIF-8 nanoparticles were assembled onto nanofibers to improve the mechanical properties and adsorption properties of the composite aerogel. The surface morphology of ZIF8-20@CPA composite aerogel is shown in Figure a3; the ZIF-8 nanoparticles grow uniformly on the lamellar structures formed by nanofibers and brought higher porosity and larger specific surface area to the composite aerogel …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, ZIF-8 nanoparticles were assembled onto nanofibers to improve the mechanical properties and adsorption properties of the composite aerogel. The surface morphology of ZIF8-20@CPA composite aerogel is shown in Figure a3; the ZIF-8 nanoparticles grow uniformly on the lamellar structures formed by nanofibers and brought higher porosity and larger specific surface area to the composite aerogel …”
Section: Resultsmentioning
confidence: 99%
“…The surface morphology of ZIF8-20@CPA composite aerogel is shown in Figure 4a3; the ZIF-8 nanoparticles grow uniformly on the lamellar structures formed by nanofibers and brought higher porosity and larger specific surface area to the composite aerogel. 32 Figure 4b−e showed the compression and recovery test pictures of the ZIF8-20@CPA composite aerogel at room temperature, in liquid nitrogen (−196 °C), at high temperature (200 °C), and in water, respectively. It was found that the composite aerogel can be quickly restored to its original state after being immersed in liquid nitrogen and compressed.…”
Section: Resultsmentioning
confidence: 99%